Multiple cycles and the Bautin bifurcation in the Goodwin model of a class struggle - Bella, Giovanni (Nonlinear Analysis: Modelling and Control, 2013)
The aim of this paper is to present the necessary and sufficient conditions for the emergence of a generalized Hopf (i.e., Bautin) bifurcation in the Goodwin’s model of a class struggle, and determine the parameter regions where multiple attracting and repelling limit cycles around the steady state may coexist.